The association between Albumin-Corrected Anion Gap (ACAG) and the risk of acute kidney injury in patients with acute pancreatitis: A retrospective analysis based on the MIMIC-IV database - Jiaxiang Bian; XiaoYang Wang; Youli Chen; Guiyang Lu; Luanluan Zhang; Xiaoyan Tu; Shuling Wang; Weibin Huang; Cunrong Chen (PLoS ONE, 2025)
Purpose Acute kidney injury (AKI), a common and severe complication of acute pancreatitis (AP), is significantly linked to patient prognosis. Albumin-corrected anion gap (ACAG) is a modified acid-base balance assessment metric with potential clinical significance in various critical illnesses. However, the role of ACAG in forecasting the risk of AKI in AP patients remains unclear. This study sheds light on the relationship between ACAG levels and AKI risk in the AP population. Methods This retrospective study utilized data from the MIMIC-IV database, including 1,552 adult patients diagnosed with AP during their stay in the intensive care unit (ICU). ACAG was calculated using a standard formula, and patients were grouped according to their ACAG levels. Cox proportional hazards and restricted cubic spline (RCS) models were employed to assess the correlation of ACAG levels with AKI risk in AP patients. The incidence of AKI was the primary outcome, and in-hospital mortality was the secondary outcome. Differences in primary and secondary outcomes between ACAG groups were evaluated through Kaplan-Meier (KM) survival analysis. Subgroup analyses were performed for examining the influence of confounding factors. Results Higher ACAG levels were significantly related to an elevated risk of AKI. The RCS model demonstrated a nonlinear correlation between higher ACAG levels and increased AKI risk in the AP cohort, and a linear association of ACAG with in-hospital death. KM survival analysis showed that patients exhibiting higher ACAG levels had poorer renal function outcomes and higher ICU mortality. Subgroup analyses further proved this correlation across varied patient characteristics. Conclusions Elevated ACAG is an independent predictor of AKI risk in the AP cohort. ACAG may be useful for early AKI risk stratification and clinical decision-making in critically ill AP sufferers.